A study of pattern of orthopedic injuries among patients attending an emergency department of Civil Service Hospital, Kathmandu Nepal - Pant, Ramesh; Lamsal, Dinesh Kumar; Thakali, Kabir; K.C., Kapil Mani; K.C., Kapil Mani (Journal of General Practice and Emergency Medicine of Nepal, 2018)
Introduction: Trauma is a common worldwide problem which has detrimental effect in the public health. It is one of the several prevailing causes of morbidity and mortality. The aim of this study is to reveal the existing nature of orthopedic injuries as seen in the emergency department and to identify potential areas of improvement for the enhancement of trauma research.Method: This study has been conducted prospectively. All the physical trauma patients visiting the emergency department of a tertiary care hospital over the period of one year were included in study. The population of the study included patients with all kinds of orthopedic injuries. Data was entered in Statistical Package for the Social Sciences (SPSS 16) to analyze, and the result of is obtained in terms of mean (percentage), appropriate plots, and chart where appropriate. The cases with pathological fracture, patients with end stage chronic diseases, and post-operative state were excluded from the study.Results:  Total of 2823 orthopedic injury patients visited the emergency in a year, which comprised 15.46% of total emergency Patients. The gender distribution was 68.4% males and 31.6% female. Only 9.8% of the patients arrived to hospital on ambulance. 34.4% of the cases arrived within one hour of trauma incident. Fall was the most common cause of injuries(40.1%) followed by road traffic accident (34.6%).The study revealed that the most common injury was fracture (33.7%), followed by sprain & strain (26.0%), laceration (19.2%), contusion with intact skin (10.0%) and dislocation (9.1%). Commonly associated visceral injury was the head injury in 12.4% cases, followed by thoracic injuries in 10.8%, abdominal injuries in 1.7 % cases.  Emergency department team alone treated and discharged 54.1% patients, whereas the remaining 45.9 % patients required specialized evaluation and treatment by other departments. Total 18.2 % patients were referred to other centers for further specialized treatment like neurosurgery, CTVS consultation, for ICU facility, for vacant admission bed, and on their wish to go to other center for further treatment.Conclusion: Fall injury and road traffic accident were the most common cause of trauma. Younger adults in their active period of life were found to be involved more in physical trauma incident. In addition to the healthcare improvement, road safety regulations should also be strengthened and enforced, which can save more lives and reduce the severity and duration of the illness.